A pathway for ZnO p-type transformation and its performance in solar cells. (1st January 2022) - Zhao, Yanfang; Yang, Haiying; Xiao, Yuanbin; Yang, Ping
Highlights: A pathway for ZnO p-type transformation for solar cells is proposed. We investigated the preparation strategy to control the quality of p-type ZnO films. We find the formula for p-type ZnO films for solar cell structure. We detect ZnO homojunction solar cell structure was successfully prepared with a photoelectric conversion rate of 0.0167%. It implies the p-type ZnO films has the potential for solar cell applications. Abstract: Aiming at the breakthrough of ZnO in solar cells, we investigate the theoretical rationality and experimental operability of its structural components. In this paper, First Principle Calculation is implemented to achieve the optimum doping ratio for ZnO p-type transformation. Then, Al-N co-doped ZnO films are prepared by magnetron sputtering. The quality of p-type ZnO films are controlled by changing the ratio of N2 O to Ar in the sputtering atmosphere. Results shown that the p-type ZnO films with excellent photoelectrical properties can be successfully obtained in the condition of N2 O:Ar = 1: 4, where the resistivity is as low as ρ = 3.678 × 10 - 5 Ω · c m, the carrier concentration is N = 1.3066 × 10 21 c m - 3, the average transmittance of the visible region is about 90%. In addition, we first explore the feasibility on the fabrication of p-type Al-N co-doped ZnO/n-type Al-doped ZnO homojunction and its application in solar cell.